Water-limited competition and the yield-density response in dryland maize (Zea mays): an ecological and economic analysis - Dewey, Caroline, author; Schipanski, Meagan, advisor; Comas, Louise, advisor; Ocheltree, Troy, committee member (Colorado State University. Libraries, 2023)
The plant dynamics of biomass production under competing resources are commonly understood through the empirical generalization of Constant Final Yield (CFY). This law has considerable utility for crop management decisions that often center on altering resources and planting density to maximize plant productivity. Dryland producers are uniquely vulnerable to variability in climactic conditions and precipitation patterns. However, most studies on yield-density relationships have focused on well-watered conditions for maize (Zea mays). In this thesis, I investigated the hypothesis that the yield-density relationship in dryland maize will approximate CFY, with the point of plateau determined by water availability (Chapter 1). This concept was tested by planting maize at a range of stand densities (20, 30, 40, 50 thousand plants/ha) under four water regimes in a semi-arid region in Colorado, USA. Plant productivity increased under greater water availability as the planting density increased. A quadratic plateau model best fit the yield-density relationship. Treatments with less water availability did not exhibit yield-limiting thresholds at the densities included. Plant functioning in terms of chlorophyll fluorescence, grain N uptake and proportional allocation to grain (i.e., harvest index) remained relatively unaffected by resource availability to the plants. Results of the study indicate dryland maize systems can reach a maximum yield while forgoing significant physiological stress. The pattern of CFY was approximated, with water availability corresponding to a higher asymptotic point at a greater population density. As a next step, a partial budget analysis was conducted to assess net returns associated with varying seeding rate and soil moisture in dryland maize cropping system (Chapter 2). Data was selected from the experimental study outlined in Chapter 1. Benefits were calculated in terms of maize grain yield. Cost estimations for each treatment included the cost of seed, representative field operations and management. Results showed that net returns responded positively to high evapotranspiration (ET) conditions. Under low ET conditions a decrease in seeding rate was more profitable. Improved soil moisture improved net returns among both seeding rates. The increase in revenue from grain yield under high ET conditions was greater than any additional costs, even though materials and services costs generally increased. Dryland producers should approach increased seeding with caution if seeking to maximize grain yield at low soil moisture.
Keywords: dryland; plant growth dynamics; resource competition; law of constant final yield; abiotic gradient; plant health